Dancing with the River: People and Life on the Chars of South Asia - Lahiri-Dutt, Kuntala; Samanta, Gopa (Yale Agrarian Studies Series, 2013)
With this book Kuntala Lahiri-Dutt and Gopa Samanta offer an intimate glimpse into the microcosmic world of "hybrid landscapes." Focusing on chars-the part-land, part-water, low-lying sandy masses that exist within the riverbeds in the floodplains of lower Bengal-the authors show how, both as real-life examples and as metaphors, chars straddle the conventional categories of land and water, and how people who live on them fluctuate between legitimacy and illegitimacy. The result, a study of human habitation in the nebulous space between land and water, charts a new way of thinking about land, people, and people's ways of life.